A practical theological assessment of the schisms in the Reformed church in Zambia (1996-2001) - Soko, Lukas (Stellenbosch : Stellenbosch University, 2010)
Thesis (DTh (Practical Theology and Missiology))--Stellenbosch Univerlsity, 2010.